Anti-Indianness In Nissim Ezekiel’S Poetry: Exploring Anti-Indianness in Nissim Ezekiel’s Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Nissim Ezekiel occupiesa unique position among Indo-Anglican poets of post-Independence era. He gave anew thought and a new outlook to Indian English Poetry and is universallyrecognized and appreciated as being one of the most notable and accomplishedIndian English language poets of the 20th century. He was against the idealismand romanticism of the earlier group of Indian writers in English. Highsounding learned words and phrases, metaphors and expressions of VictorianEnglish, long and complex syntax, etc usually mark formal Indian writing inEnglish. . He comes of a Jewish family who had migrated to India and settleddown in Bombay where Nissim was born, brought up and educated. As a poet he hasobserved and experienced much of the Indian life. He tried to look at anytypical Indian situation with an Indian attitude and insight. But his poetryseems to be a comment on various aspects of Indian society. He has largelyrebelled against the Indian way of life and Indian way of speaking the Englishlanguage. The present article explores this anti-Indianness in the poems ofNissim Ezekiel.